The Effect of Rotational Speeds on the Microstructural and Mechanical Properties of Friction Stir Welded Dissimilar Aluminum Alloy Plates - NGAKE, Tankiso Lawrence; MJALI, Kadephi Vuyolwethu (Engineering Transactions, 2024)
The aim of this study is to investigate the effects of rotational speed on the quality of welds, microstructure, and mechanical properties in friction stir welding of dissimilar aluminum alloys (AA5083 and AA6082). Different samples were produced by varying the rotational speeds to 900, 1000, 1130, and 1260 rpm. The microstructure of the weld joints was evaluated by optical microscopy, while microhardness and tensile stress were examined using a microhardness tester and tensile tester. The microstructural analysis indicates fine equiaxed recrystallized grains in the stir zone for all the samples, regardless of rotational speeds. However, the macrographs indicated the development of voids with increasing rotational speeds. The lowest microhardness was observed in the stir zone for all the samples. The ultimate tensile stress decreased as rotational speed increased. Overall, the lowest rotational speed of 900 rpm yielded optimal results, with minimal defects and higher tensile strength.